The impact of reimbursement negotiations on cost and availability of new pharmaceuticals: Evidence from an online experiment - Dominik J. Wettstein; Stefan Boes (Health Economics Review, 2020)
Background: The necessity to measure and reward "value for money" of new pharmaceuticals has become central in health policy debates, as much as the requirement to assess the "willingness to pay" for an additional, qualityadjusted life year (QALY). There is a clear need to understand the capacity of "value-based" pricing policies to impact societal goals, like timely access to new treatments, sustainable health budgets, or incentivizing research to improve patient outcomes. Not only the pricing mechanics, but also the process of value assessment and price negotiation are subject to reform demands. This study assesses the impact of a negotiation situation for lifeextending pharmaceuticals on societal outcomes. Of interest were general effects of the bargaining behaviour, as well as differences caused by the assigned role and the magnitude of prices. Methods: We ran an online experiment (n = 404) on Amazon Mechanical Turk (MTurk). Participants were randomly assigned into four treatment groups for a reimbursement negotiation between two roles (health minister, pharma representative) in two price framings. Payoff to players consisted of a fixed salary and a potential bonus, depending on their preferences, their price offer and the counter offer of a randomly paired negotiation partner. Success had real social consequences on other MTurk users (premium payers, investors) and via donations to a patient association. Results: Margins between reservation prices and price offers increased throughout the game. Yet, 47% of players reduced at least once and 15% always their bonus probability to zero in favour of an agreement. 61% of simulated negotiation pairs could have reached an agreement, based on their preferences. 63% of these were successful, leaving 61% of patients with no access to the new treatment. The group with "real world" prices had lower prices and less agreements than the unconverted payoff group. The successful markets redistributed 20% of total assets from premium payers to investors over five innovation cycles. Conclusions: The negotiation situation for pharmaceutical reimbursement has notable impact on societal outcomes. Further research should evaluate policies that align preferences and increase negotiation success.
Keywords: 330; Reimbursement; Negotiation; Willingness to pay; Willingness to accept; Social preferences; Health insurance; QALY; Value-based pricing; Health technology assessment